PENGARUH KEPEMIMPINAN, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM KOTA SEMARANG - Dwi Hari Prasetiyo, 0735020726 (Students Journal of Economic and Management, 2013)
The purpose of the study to examine the influence of leadership, motivation, and work environment on employee performance on local water companies Semarang. The sample used in this study were 90 respondents to the data collection methods used in this study by distributing a questionnaire to the respondent in order to obtain information. The data were analyzed using analysis to test the validity of the question items using the product moment, and reliability of the instrument, regression analysis, to examine the effect of partially magnitude of each independent variable as follows Y = .0,231. X1-0.223. X2 +0.578. X3 of regression equation is known that the regression coefficient (Î²) leadership (X1) = 0.231, perceptions of motivation (X2) = 0.223 work environment (X3) = 0.578. The results of the study indicate that the independent variables that have a dominant influence on performance is variable and the work environment that have the smallest influence is motivation. Results of calculation of the coefficient of determination Adjusted R Square is equal to 0645 or by 64.5% means that 64.5% change in the dependent variable Y (employee performance) can be explained by the influence of leadership variables (X1), motivation (X2) and work environment (X3 ), while the remaining 36.5% dipengaruh by other variables that are not tested or described in this research model Keywords: Leadership, Motivation, Work Environment and employee performance